1999
DOI: 10.1289/ehp.99107303
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile hypothyroidism among two populations exposed to radioiodine.

Abstract: We found an epiic of juvenile hypothyroidism among a population of se-defied "donwinders" living near the Hanford nuclear facility located in southeast Washington State. The episode followed massive releases of 13L Self-reported data on 60 cases of juvenile hypothyroidism (<20 years of age) among a group of 801 Hanford downwinders are presented, as well as data concerning the thyroid status of approximately 160,000 children eTosed to radioiodine before 10 years of age as a result of the 26

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 5 publications
0
24
0
Order By: Relevance
“…Some previous studies of hypothyroidism or TSH levels among children exposed to radioiodines from Chernobyl fallout have reported higher TSH concentrations in exposed subjects compared with unexposed controls (Goldsmith et al 1999; Quastel et al 1997; Vykhovanets et al 1997), though others have not (Agate et al 2008; Pacini et al 1998; Vermiglio et al 1999). Almost all above-mentioned studies were based on small samples (from 53 to 804 exposed subjects) or lacked estimates of individual 131 I thyroid doses.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Some previous studies of hypothyroidism or TSH levels among children exposed to radioiodines from Chernobyl fallout have reported higher TSH concentrations in exposed subjects compared with unexposed controls (Goldsmith et al 1999; Quastel et al 1997; Vykhovanets et al 1997), though others have not (Agate et al 2008; Pacini et al 1998; Vermiglio et al 1999). Almost all above-mentioned studies were based on small samples (from 53 to 804 exposed subjects) or lacked estimates of individual 131 I thyroid doses.…”
Section: Discussionmentioning
confidence: 90%
“…Some earlier studies reported an increase in thyroid-stimulating hormone (TSH) levels and the prevalence of juvenile hypothyroidism among children exposed to 131 I following Chernobyl (Goldsmith et al 1999; Quastel et al 1997; Vykhovanets et al 1997), but other studies did not (Agate et al 2008; Kasatkina et al 1997; Pacini et al 1998; Vermiglio et al 1999). An increased prevalence of thyroid autoimmunity has been reported (Kasatkina et al 1997; Pacini et al 1998; Vermiglio et al 1999), although it seemed to be transient with no long-term effect on thyroid function (Agate et al 2008).…”
mentioning
confidence: 99%
“…Other studies of populations of children exposed to I-131 from Chornobyl fallout have focused on hypothyroidism, which is a far more common form of thyroid dysfunction, but few have reported positive results (13,14). Although the exposure in question was not internal I-131 radiation, a recent publication based on atomic bomb survivors in Hiroshima and Nagasaki who participated in a comprehensive thyroid screening study (33) reported a nonsignificant elevated EOR/Sv for hyperthyroidism in those exposed to external radiation at 10 years of age (EOR/Sv=0.49, 95% CI: −0.06–1.69, P =0.10).…”
Section: Discussionmentioning
confidence: 99%
“…There have also been limited reports on risk of functional thyroid abnormalities related to Chornobyl fallout, although with mixed results and methodological limitations (10,11,12,13,14,15,16). We have been studying thyroid function in a cohort of ~13,000 persons exposed to I-131 in Ukraine under the age of 18 years, who had thyroid radioactivity measurements taken within eight weeks of the accident and who were screened by clinicians using a standardized protocol.…”
Section: Introductionmentioning
confidence: 99%
“…The results of post-Chornobyl studies have been mixed. While some studies reported a significant upward shift in TSH levels and increased rates of juvenile hypothyroidism in children living in radionuclide contaminated areas (4648), the remaining ecological studies were negative (4952). In a recent cohort study of 11,853 individuals under the age of 18 years at the time of the Chornobyl accident living in an area of mild-to-moderate iodine deficiency (53), the overall prevalence of subclinical hypothyroidism was about 6% (54), an estimate that is somewhat higher than that reported for the U.S. population of comparable age (12).…”
Section: Thyroid Diseasesmentioning
confidence: 99%